2019
DOI: 10.3389/fnbeh.2019.00032
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cannabinoids Produce Robust Anxiety-Like and Locomotor Effects in Mice, but Long-Term Consequences Are Age- and Sex-Dependent

Abstract: The rise in cannabinoid legalization and decriminalization in the US has been paired with an increase in adolescents that perceive marijuana as a “no risk” drug. However, a comprehensive review of human literature indicates that cannabinoid usage may have both beneficial and detrimental effects, with adolescent exposure being a critical window for harming cognitive development. Although the cannabinoids Δ9-tetrahydrocannabinol (THC) and cannabidiol (CBD) are often used together for recreational and medical pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 73 publications
5
44
2
3
Order By: Relevance
“…1C). This dose was based on previous studies using low to high ranges of THC in mice (Trexler et al, 2018;Kasten et al, 2019). Moreover, this dose used has been shown to elevate plasma levels of THC in rodents (> 100 ng/mL) similar to those found in humans smoking cannabis (Huestis, 2007;Zuurman et al, 2008;Nguyen et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…1C). This dose was based on previous studies using low to high ranges of THC in mice (Trexler et al, 2018;Kasten et al, 2019). Moreover, this dose used has been shown to elevate plasma levels of THC in rodents (> 100 ng/mL) similar to those found in humans smoking cannabis (Huestis, 2007;Zuurman et al, 2008;Nguyen et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Kasten et al (2019) [72] found that 5 and 10 mg/kg doses of THC in adult mice reduced total locomotion. In the 5 mg/kg adult group this was significantly correlated with reduced time in the centre of the open field indicating an anxiogenic-like response.…”
Section: Open Field (Of) Testmentioning
confidence: 99%
“…26 Initial response to cannabis, THC, and other cannabinoid receptor 1 (CB1R) agonists has been measured across a range of doses among several inbred and outbred mouse strains (Table 1). [27][28][29][30][31][32][33][34][35] However, few of these studies have directly compared strain differences in response and most do not include females, thus preventing analysis of sex differences. Despite marked variation among individuals in the acute response to cannabis in humans, 36 little is known about the genetic factors mediating differential response or how initial sensitivity and tolerance may contribute to risk of CUD.…”
Section: Introductionmentioning
confidence: 99%